(untitled) (Research, Society and Development, 2022)
The production models created by the industry throughout the twentieth century are now put in check in the face of technological developments and the new digital transformation of manufacturing, known as Industry 4.0 (I4.0). Although many advantages and possibilities are still perceived from this transition, there is little discussion about the business models that will best adapt to this context, making it opportune to review the business models that emerge or are adapted to this new paradigm. This study aims to study the business models related to I4.0, in order to understand how these models support the value creation and how the alignment takes place with the strategy, in addition to identifying gaps for future studies. The methodology used was a systematic literature review, using bibliometrics and network and content analysis. This research had a descriptive purpose, making use of secondary sources through bibliographic survey, with consultation of SCOPUS and Web of Science databases. The sample of 149 publications was analyzed, allowing the discussion of business models in the context of Industry 4.0. Likewise, the analysis of the selected articles made evident the wide scope for future research. It is concluded from the research, that business models in the context of Industry 4.0 point to sustainable industrial value creation and tend to be directed to consumers, with a flexible and customized demand offer, passing by the lot size one, mass customization, when companies will shift their focus from marketing their products to providing solutions to specific customer desires.